Anti-Terrorism Cooperation of the Shanghai Cooperation Organization - Shiru Mei (Studies in Social Science & Humanities, 2024)
In the 13 years since its founding, the SCO has always focused on counter-terrorism, both for its own organizational role and for the reasons of its member states. The SCO has always achieved remarkable results in counter-terrorism work, which has shown the world its strength. However, as the organization continues to expand, the SCO also faces significant challenges in counter-terrorism cooperation due to inherent problems among its members and the identification of specific concepts.